HUBUNGAN MENGKONSUMSI MAKANAN KARIOGENIK DAN POLA MENYIKAT GIGI DENGAN KEJADIAN KARIES GIGI PADA ANAK USIA SEKOLAH - Setyaningsih Rahayu; Luki Indra Asmara (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2018)
Background: Dental caries are often found in school age, caused by consume cariogenic foods and wrong brush teeth pattern. Some foods like candy, chocholate, sweat breads can make children have a dental caries. The Purpose : To determine the relationship between consume cariogenic food and brush teeth pattern with the incidence of dental caries in school age. Subjects: The population in this study were all students at class I-III in SDN I and II Gedangan Sukoharjo as many as 205 students.The sample in this study is student at class I-III as many as 150 students used a sampling technique quota sampling. Methods: This research is an analytical research design correlation to determine the relationship between consume cariogenic food and brrush teeth pattern with the incidence of dental caries in school. Results: From the statistical test bivariate relationship of each independent variable and dependent variable using the chi-square test results p: 0.001. As for the results of multivariate statistical test values obtained Nagelkerke R Square of 56.6%. Conclusion: A variable level of consume cariogenic food and brush teeth pattern together can influence the incidence of dental caries in children school age of 56.6% and the remaining 43.4% influenced by other variables. Keywords: Smoking, disruption of sleep patterns, teen age